PENGARUH DEBT TO EQUITY RATIO (DER) DAN RETURN ON ASSET (ROA) TERHADAP HARGA SAHAM - Dini Arifian; Siti Suhaenah (The Asia Pacific Journal Of Management Studies, 2022)
The objectives of this study are (1) to determine the effect of Debt to Equity Ratio (DE) on stock prices in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period, (2) to determine Return on Assets (ROA) to share prices in food and beverage sub- sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The method used in this research is descriptive and quantitative research methods. The sampling technique used by purposive sampling is a sample selected using certain considerations in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016- 2020 period which can be accessed or downloaded directly on the official Stock Exchange website. Indonesia (IDX) www.idx.co.id and https://finance.yahoo.com. Testing of this research was carried out by using the Classical Assumption Test, then analyzed by the Correlation Test and Multiple Linear Regression Test using the SPSS V.20 program. Conclusion Debt to Equity Ratio (DER) has no effect on stock prices, Return on Assets (ROA) affects stock prices, Debt to Equit Ratio (DER), Return on Assets (ROA), stock prices occur simultaneously .